Extrato de própolis na alimentação de cães - Rivera, Nancy Lorena Montaño (2011)
The experiment to evaluate the propolis utilization in dogs' diet was carried out in three stages. The first stage was based on two digestibility trials with aim of evaluating effect of propolis inclusion in different concentrations and extracts on apparent digestibility of dry mater (DM), crude protein (CP), acid ether extract (AEE), nitrogen free extractives (NFE), and metabolizable energy (ME), of diets for adult Beagles. In both trials ten dogs were distributed in Latin square design 5x5 (five diets versus five periods) with two replicates per period. At first trial were used different extracts SLNC106, SLNC206, SLNC109 and SLNC209, plus reference diet without propolis' addition. For second trial, the propolis extract SLNC206 was added in different concentrations: 0, 20, 40, 60 and 80mL dilutes in two liters of soybean oil and added to 75 kg of the diet. In the first trial the inclusion SLNC209 extract decreased apparent digestibility coefficient (ADC) of DM. In the second trial, the increasing inclusion of propolis extract improved linearly ADC of CP, AEE, NFE, DM and ME diets. For second and third stage, it was used a commercial diet (Nova D+), with or without propolis extract (SLNC206/SL49(PI)) inclusion, which provided a total flavonoid content of 0.11 mg/kg of bw per day. The second stage had objective to evaluate the effect of propolis extract on diet intake; body condition: body weight (bw), body score and tissue subcutaneous fat in the lumbar region; biological condition: index proliferation of lymphocytes, vaccination response against canine distemper vírus, hemograme, serum alkaline phosphotasis, creatinine, total cholesterol and triacylglycerol (TAG) and faeces characteristics: score, odour and microbiology. Sixteen beagle dogs, 11 months-old each, were used for five months, randomly divided in two groups, control diet versus propolis extract diet. The group fed with propolis extract showed a greater reduction in (PI) Patent: PI 05063930. weight, thickness of the subcutaneous fat and total cholesterol at the end of the experiment. Higher values of colony-forming unit in faeces of dogs fed with propolis extract diet were observed. However, the characteristics: intake, body score, clinical assessment, vaccine response, lymphocyte proliferation index, serum alkaline phosphatasis and creatinine, score and faecal odour did not differ between both groups. Third stage evaluated, in dogs, the effect of the propolis extract inclusion in the dog diet on the palatability and first choice. Twenty dogs of different breeds were used, Beagle, Siberian Husky, Labrador Retriever and Basset Hound. The trial lasted three days, totalising 60 repetitions. The propolis extract inclusion in diet increased the palatability and higher first choice percentage.